2022
DOI: 10.1186/s13023-022-02471-x
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset cblC deficiency around puberty: a retrospective study of the clinical characteristics, diagnosis, and treatment

Abstract: Background cblC deficiency is the most common type of methylmalonic aciduria in China. Late-onset patients present with various non-specific symptoms and are usually misdiagnosed. The purpose of this study is to investigate the clinical features of patients with late-onset cblC deficiency and explore diagnosis and management strategies around puberty. Results This study included 56 patients (35 males and 21 females) with late-onset cblC deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The MMA concentration was identified by MS-MS using specific cutoff values for propionylcarnitine (C3) and its ratio with acetylcarnitine (C2). This patient (P5) with cblC-MMA was missed because her C3 level and C3/C2 were normal but with compound heterozygous for two missense variants (c.482G>A/c.565C>T) of the MMACHC gene; the variant c.482G>A is associated with milder disease [ 24 ] and late onset [ 25 ]. Therefore, these two missing patients were very difficult to avoid by MS/MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMA concentration was identified by MS-MS using specific cutoff values for propionylcarnitine (C3) and its ratio with acetylcarnitine (C2). This patient (P5) with cblC-MMA was missed because her C3 level and C3/C2 were normal but with compound heterozygous for two missense variants (c.482G>A/c.565C>T) of the MMACHC gene; the variant c.482G>A is associated with milder disease [ 24 ] and late onset [ 25 ]. Therefore, these two missing patients were very difficult to avoid by MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…The variant c.80A>G is reported to be associated with late-onset diffuse lung disease (DLD) [ 26 ] and prominent renal complications, and the most frequent renal pathological manifestation is thrombotic microangiopathy [ 27 ]. The variant c.80A>G should be considered to indicate disease of the cardiovascular system [ 25 ]. Analysis of the composition of the MMACHC gene variants in the healthy population ( Supplemental Figure S2 ) revealed the four most common variants to be c.609G>A, c.658_660delAAG, c.482G>A, and c.80A>G, which is basically consistent with reported data for Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Later onset patients or adults may show cognitive abnormalities such as progressive encephalopathy, movement disorders, speech disorders, learning di culties, psychoneurotic symptoms, dementia, and executive dysfunction. It can also manifest as spinal cord degeneration and spinal cord thrombosis (5,6). It can also impact the optic nerve (7), resulting in impaired vision.…”
Section: Introductionmentioning
confidence: 99%
“…According to the age of onset, cb1C can be divided into early-onset (onset within 1 year) and late-onset (after 4 years), with different clinical manifestations according to the type and location of gene mutation (9). Early onset was associated with a higher mortality risk (5). Common MRI signs include myelination dysplasia, brain atrophy, lateral ventricle dilatation, and bilateral pallidum symmetry signal abnormalities (10).…”
Section: Introductionmentioning
confidence: 99%
“…In mainland China, cblC defects are the main type of combined methylmalonic aciduria (MMA) and homocystinuria ( Cui et al, 2018 ). Studies have found that the prevalence of cb1C deficiency in Shandong province of China was 1/3,920 from 2011 to 2014 ( Han et al, 2016 ), however, the nationwide prevalence of cblC deficiency is unclear ( Chen et al, 2022 ). In the case of combined defects (cblC, cblD, and cblF), both MMA and homocysteine accumulate, and these defects are vital characteristics of patients with MMA.…”
Section: Introductionmentioning
confidence: 99%